Glymphatic system function in patients with ischemic stroke evaluated by the DTI-ALPS method: a comprehensive review - Zeng, Lichuan; Yin, Zihan; Li, Wei; Wang, Xiao; Zhang, Yaodan; Xie, Mingguo; Zhao, Ling (Frontiers in Neurology, 2025)
The glymphatic system is a glial-dependent waste clearance pathway in the central nervous system (CNS) of vertebrates that exploits the perivascular compartment between the vascular basement membrane (outermost wall of blood vessels) and astrocytic vascular endfeet to facilitate exchange between cerebrospinal fluid and interstitial solutes throughout the brain. This intricate network plays a vital role in the efficient elimination of metabolic waste and the regulation of water transport within the brain. Ischemic stroke, characterized by interrupted or reduced blood supply to a specific region of the brain, is a major cause of disability and mortality. Impairment of the glymphatic system is implicated in the pathophysiological process of stroke, including disruption of the blood–brain barrier, formation of cerebral edema, induction of neuroinflammation, and accumulation of neurotoxic factors. Various studies have demonstrated asymmetry and impairment of glymphatic function during ischemic stroke. Diffusion tensor image analysis along the perivascular space (DTI-ALPS) using diffusion magnetic resonance imaging is an effective method for evaluating glymphatic system function by examining interstitial fluid dynamics within the human brain. In this study, we provide an overview of putative mechanisms mediating the role of the glymphatic system in ischemic stroke pathophysiology, with a strong focus on discussing DTI-ALPS applications in assessing changes in glymphatic function following an ischemic stroke.